1971
DOI: 10.1002/polc.5070360121
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and the prolate ellipsoid model applied to low molecular weight cellulose triacetate fractions

Abstract: Cellulose triacetate of molecular weight 5,600, obtained by acetolysis, and separated into 15 fractions by preparative permeation chromatography, was analyzed for intrinsic viscosity, number average, and weight average molecular weight. Glucose pentaacetate, cel‐lobiose octaacetate, and cellotriose hendecaacetate are also included in the analysis. The axial ratios of a prolate ellipsoid calculated from the viscosity of the low DP CT A fractions, when compared to a molecular model and to the fully extended cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1974
1974
1999
1999

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…4) and especially C-5, C-3, and C-2. It probably indicates a strong interaction of the hydrazine molecule with OH(2) and OH (3). Apart from this strong interaction, there is no evidence of a chemical reaction of hydrazine and cellulose and it may be concluded that hydrazine is a real solvent of cellulose.…”
Section: Hydrazine Solutionmentioning
confidence: 96%
“…4) and especially C-5, C-3, and C-2. It probably indicates a strong interaction of the hydrazine molecule with OH(2) and OH (3). Apart from this strong interaction, there is no evidence of a chemical reaction of hydrazine and cellulose and it may be concluded that hydrazine is a real solvent of cellulose.…”
Section: Hydrazine Solutionmentioning
confidence: 96%